Electronic medical records as a replacement for prospective research data collection in postoperative pain and opioid response studies. (March 2018) - Lingren, Todd; Sadhasivam, Senthilkumar; Zhang, Xue; Marsolo, Keith
Highlights: We evaluate the potential for EMR data to replace prospective research data collection. We compared the completeness and agreement of EMR and study variables for 358 patients enrolled in a prospective study. Variables compared included study outcomes and adverse events. Completeness values were greater than 96%. For adverse event variables, we found slight to substantial agreement. Using EMR data as a replacement for prospective research data collection shows promise for some variables, but more study is needed. Abstract: Background and aim: Many clinical research studies claim to collect data that are also captured in the electronic medical record (EMR). We evaluate the potential for EMR data to replace prospective research data collection. Methods: Using a dataset of 358 surgical patients enrolled in a prospective study, we examined the completeness and agreement of EMR and study entries for several variables, including the patient's stay in the post-operative care unit (PACU), surgical pain relief and pain medication side effects. Results: For all variables with a completeness percentage, values were greater than 96%. For the adverse event variables, we found slight to substantial agreement (Cohen's kappa), ranging from 0.19 (nausea) to 0.48 (respiratory depression) to 0.73 (emesis). Conclusion: The potential to use EMR data as a replacement for prospective research data collection shows promise, but for now, should be evaluated on a variable-by-variable basis.